Community of weeds in a groundnut crop (Arachis hypogaea) and its relationship to the rat Sigmodon hirsutus in Alajuela, Costa Rica - Monge, Javier (2009)
We compared the efficiency of traps of different size in catching rats, Sigmodon hirsutus, and determined the causes that affect the proper functioning of these traps. The study was conducted in a plantation of peanut, Arachis hypogaea, of 0.7 ha, with a sample area of 0.49 ha, and a grid-shaped arrangement of traps for a total of 539 and 294 traps night, small and large, respectively. The main reason for inade-quate functioning of the traps was the absence or scarcity of bait, followed by the presence of ants; activation, removal or turning over of traps; flooding of traps, and capture of other species. The success of catches in large traps was 9.9%, while in the smaller ones only 4.4%. Both types of trap succeeded in capturing rodents of most classes of length and weight, without evidence of a significant difference in type of rodent, accor ding to length and weight, captured by the traps large, whereas small showed a limited ability to capture individuals of higher body weight. However, small traps showed limitations in the capture of individuals of larger size and weight so it is assumed that the use of only small snap traps may bias the results in population studies of this species of rodent.